PENGEMBANGAN MEDIA SCRAPBOOK PADA PEMBELAJARAN IPA - Veronica, Indah; Whyu Pusari, Ratna; Setiawardana, M.Yusuf (Universitas Pendidikan Ganesha, 2018)
In particular learning in natural science subjects, there are still a number of students who concentrate less on science, even less interested in the learning process, with the problem the researchers conducted research on scrapbook development in science learning. It is expected that with the development of these media students can be motivated and more enthusiastic in learning. The object and subject of this research are third grade students of elementary school. The data of this research are the results of media validation by material experts, media experts, and practitioners and the siwa III response to the developed media. This research uses Research and Development (R & D) research methodology and Borg and Gall development model. Media relevance is obtained from assessment by media experts and material experts. Based on the results of scrapbook media development research in science learning, the media developed proved valid based on the results of media validation by experts and practitioners. Learning media can also be accepted by students as evidenced by student responses taken by questionnaire responses used by researchers. Keywords: Development, Media, Scrapbook